Enhancing Students’ Literacy and Numeracy through Learning Model Based on the Panca Pramana Cycle - I Gede Astawan; Ni Made Dyan Anggreni; Rohmatullah (Jurnal Ilmiah Sekolah Dasar, 2025)
Elementary school students still struggle to achieve literacy and numeracy competencies, requiring effective learning innovations. One approach that can be used is the Panca Pramana learning cycle-based learning model, which is applied to local philosophy and emphasizes an active and meaningful learning process. This study aims to analyze the differences in literacy and numeracy skills between students who participate in learning with the Panca Pramana learning cycle-based learning model and students who participate in learning with conventional learning models. This study uses a quasi-experimental approach with a control group design and an experimental group that are given a pretest and posttest. The research subjects are elementary school students selected through group random sampling techniques, resulting in one class as the experimental group and one class as the control group. The research data consist of literacy and numeracy skills collected through validated literacy and numeracy tests. Data analysis was carried out through descriptive analysis and inferential analysis using multivariate tests. The results of the study indicate that there are significant differences in literacy and numeracy skills, both partially and simultaneously, between students who participate in learning with the Panca Pramana learning cycle-based learning model and students who participate in conventional learning. These findings indicate that the Panca Pramana learning cycle-based learning model is effective in improving students' literacy and numeracy skills. The implications of this research emphasize the importance of integrating local philosophical values into learning innovations as a strategy to improve learning quality and support the more meaningful development of students' basic competencies.